Changeability of spatial and temporal gait parameters measured on a treadmill with the use of a 3d ultrasound-based movement measuring system - Hagner-Derengowska, Magdalena; Dylewski, Michał; Dawidziuk, Joanna; Hagner, Wojciech (Medical and Biological Sciences, 2012)
Introduction. Subclinical measurements of psychomotor functions are being used for assessment of mental functions by finding relations with these functions. This study aims to assess the influence of a therapeutic dose of methadone on psychomotor speed in HIV(+) and HIV(-) subjects treated in substitution therapy. Materials and methods. 73 patients [32 HIV(-) and 41 HIV(+)]treated with methadone for an average of 54 months, were examined. The assessment was conducted twice: before and about 1.5 hours after the administration of a therapeutic dose of methadone. Trail Making Test A (TMT A) was completed. The test sheet was placed on a graphic tablet. Execution time was measured in both parts of the test. Results. It was found that the average time of TMT A test completion before methadone administration in HIV(-) subjects is statically significantly shorter than in HIV(+) ones. However, after methadone administration psychomotor speed, measured by the TMT A test, is not statistically significantly different in HIV(-) subjects treated in substitution therapy as compared to HIV(+) individuals. Subjects with HIV (+) performed TMTA test statistically significantly faster after a single dose of methadone. Conclusion. A therapeutic dose of methadone in subjects infected with HIV virus can have an effect on the improvement in psychomotor performance. Interactions of antiretroviral drugs and methadone can lead to changes in the concentration of methadone in the body influencing the regulation of psychomotor activity at the same time.